Implementasi Gaya Kepemimpinan Partisipatif pada Pendidikan Dasar di Era Pandemi Covid-19 - Ibrahim, Asenan Erik; Alfiah, Luluk; Roesminingsih, Erny (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The issue discussed in this article is related to the participatory leadership style of a school principal in the elementary education system during the Covid-19 pandemic. The objectives of this researchwere: 1) analyzing the participatory leadership style applied in the education field, 2) analyzing the extent to which participatory leadership style could be the best alternative in the elementary education systemduring the COVID-19 pandemic. The method used in this writing was a literacy study, in which the author reviewed 20 journal articles and additional reference sources from 5 books. From these various sources, it was finally possible to bring scientific arguments from the researcher. From the results of the study of the existing reference sources, it showed that: 1) the participatory leadership style in education was a leadership style that focused on the efforts of a leader, in this case was the principal,to involve the participation of its members in every process in the organization, including the decision-making process. 2) The participatory leadership style in education field could be used as the best alternative in the elementary education system in the COVID-19 pandemic because in this difficult situation, leaders needed to apply the principles of acceptance, delegation, and participation so that all challenges could be handled well, including in elementary education field.